1981
DOI: 10.1039/dt9810000506
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of di-µ-ethanethiolato-µ-sulphido-bis[dichloro-(tetrahydrothiophen)tungsten(IV)(W–W)]: a confacial bioctahedral complex with a tungsten-to-tungsten bond

Abstract: The complex [(C,H,S)CI,W(p-S) (p-SEt),WCI,(SC,H,)] has been prepared by reaction of [WCI,(C,H,S),] with one mole equivalent of SiMe,(SEt) in CH,CI, solution. A single-crystal X-ray diffraction study shows that the molecule has a confacial bioctahedral structure with a W-W bond length of 2.524(1) A. The structure has been solved by heavy-atom methods from automated diffractometer data, and refined to R 0.025 (R' 0.037) for 1 593 reflections. The complex crystallizes in the orthorhombic system, space group Pnam,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
1

Year Published

1981
1981
1996
1996

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
1
6
0
1
Order By: Relevance
“…The implication of this observation ture severely distorted by a strong metal-metal is that the interaction is indeed due to a direct interaction. metal-metal double bond, as was previously sugThere are two differences, however, in the gested (2). The distance is almost identical to that geometry of the three W(p-S)(p-SEt),W moieties.…”
Section: Fig 2 Ortep View Of the Anion [C13w(p-s)(p-set)wc112-supporting
confidence: 59%
See 1 more Smart Citation
“…The implication of this observation ture severely distorted by a strong metal-metal is that the interaction is indeed due to a direct interaction. metal-metal double bond, as was previously sugThere are two differences, however, in the gested (2). The distance is almost identical to that geometry of the three W(p-S)(p-SEt),W moieties.…”
Section: Fig 2 Ortep View Of the Anion [C13w(p-s)(p-set)wc112-supporting
confidence: 59%
“…Une Ctude par diffraction de rayons X sur un monocristal montre que cette molCcule a une structure bioctakdrique concafaciale avec une longueur de liaison de 2,52(2) A. On a rCsolu la structure par la mCthode des atomes Examples of tungsten(1V) complexes with well-(C~HSS)I, 3 (2). The starting material, WCI4(MezS)2?…”
unclassified
“…Hence, by replacing CI by RS ligands in a high oxidation state Mo or W complex, reductive elimination of R 2 S 2 will leave coordinatively unsaturated metal centers in intermediate oxidation states, which are ideal precursors for cluster formation. This procedure proved to be a fruitful method for synthesizing binuclear complexes of W(IV), and, in some cases, mixed valent W(IV)/W(III) products were isolated (3)(4)(5)(6). Even in these reactions the dealkylation of thiolate ligands to give sulfido complexes is frequently observed, and the products from such reactions are extremely unpredictable.…”
Section: S-dealkylation Of W(vi) Thiolates: Evidence For Carbocation mentioning
confidence: 96%
“…This suggested an intermediate oxidation state of Mo or W, which of course would also be consistent with the +4 oxidation in an MS 2 phase. This limited the choice somewhat, and led to successful reactions between Cp 2 ZrH 2 and Mo(S l Bu) 4 , and Cp 2 NbH 3 and Mo(S l Bu) 4 respectively. The initial reaction was carried out with Cp 2 ZrH 2 , and Mo(S l Bu) 4 with benzene as solvent (72).…”
Section: Intermolecular Reactions Between Hydride and Thiolate Ligandsmentioning
confidence: 98%
“…1). Recent studies in our laboratory have shown that the W-SR group in complexes of tungsten(1V) is unstable as a terminal entity (2)(3)(4)(5). By metathesis of WC14L, (L = Me2S; C4H8S) with SiMe3(SR) (R = alkyl, aryl), the intermediates WC4-,(SR),,L2, 2, have been prepared via the equation: \ 2 can undergo degradation by one of two observed pathways, depending on the stoichiometry (i.e.…”
mentioning
confidence: 99%